Unternehmensanalyse im Zeichen zunehmender Internationalisierung der deutschen Wirtschaft - Hans Friderichs (Wirtschaftsdienst, 2014)
Die Verbundaktivitäten deutscher Unternehmen gewinnen seit geraumer Zeit an Bedeutung. Darin schlägt sich nieder, dass sie funktional stärker differenziert und spezialisiert sowie zunehmend internationalisiert sind. Nachdem sich die globale Arbeitsteilung geändert hat, stößt die klassische Unternehmensabschlussstatistik, die sich nur auf den inländischen Raum bezieht, an ihre Grenzen. Sowohl auf nationaler als auch auf internationaler Ebene gibt es Initiativen, die statistischen Lücken in der Darstellung des Unternehmenssektors zu schließen. – – Economic analyses of the corporate sector provide an important contribution to evidence-based economic policymaking. However, these analytical approaches, which are based on the separate financial statements prepared by domestic enterprises, are finding it more and more difficult to accommodate the increasingly important role which the exchange of goods and services among enterprises and the growing financial ties among group enterprises plays for economic activity in the corporate sector. Since the traditional corporate financial statement statistics can no longer paint a complete picture of the increasingly globalised nature of the German economy, the Deutsche Bundesbank recently began building up a database using data extracted from selected consolidated financial statements, as these accounts also capture the share of value added generated by external subsidiaries and affiliates of German enterprises abroad. Substantially broadening the analytical spectrum in this manner is crucially important for an open economy.
Keywords: F23; G32; L16; 330; Multinationales Unternehmen; Internationale Arbeitsteilung; Betriebliche Statistik; Außenhandelsstatistik